Geometry Presorting for Implicit Object Space Partitioning - Eisemann, M.; Bauszat, P.; Guthe, S.; Magnor, M. (Computer graphics forum, 2012)
We present a new data structure for object space partitioning that can be represented completely implicitly. The bounds of each node in the tree structure are recreated at run‐time from the scene objects contained therein. By applying a presorting procedure to the geometry, only a known fraction of the geometry is needed to locate the bounding planes of any node. We evaluate the impact of the implicit bounding plane representation and compare our algorithm to a classic bounding volume hierarchy. Though the representation is completely implicit, we still achieve interactive frame rates on commodity hardware.